Effects of alkanols on the solubilization of methanol and ethanol in red palm oil for biofuel - Dzulkefly, K.; Lim, W.H.; Hamdan, S.; Norlizah, S. (Japan Oil Chemists' Society, 2002)
Solubilizations of methanol and ethanol in crude palm oil (CPO) and red palm oil (RPO) were studied by using different hydrocarbon chain-length alkanols (C4-C12) as solubilizers. Ternary phase diagrams of oil/methanol/alkanol and oil/ethanol/alkanol were constructed to determine the solubilization (isotropic) region. Results showed that the solubilization of methanol and ethanol is more favourable in unsaturated RPO than in saturated CPO in the presence of long-chain alkanols. The relatively large isotropic regions were formed with long-chain alkanols in both the methanol and ethanol systems. The order of decreasing isotropic regions in both methanol and ethanol systems was dodecanol > decanol > octanol > octan-2-ol > hexanol > pentanol > butanol > t-butanol. The branched chain alkanols and mixed oleyl alcohol/alkanol do not promote solubilization. Cold-stability test has shown all isotropic solutions were stable at 24°C for both methanol and ethanol systems. Kinematic viscosity of the selected isotropic solutions increased with the increase in both the chain length and percentage of alkanols. Long-chain alkanols (dodecanol, decanol and octanol) showed a steady increased in kinematic viscosity with increasing alkanol content. Solubilization of RPO/methanol/mediumchain alkanols (butanol, pentanol and hexanol) systems significantly reduced the kinematic viscosity of RPO from 43.7 mmV to the range allowable for No. 2 diesel fuel (1.9-4.1 mmV at 40.0°C).